Analisis Kelayakan Investasi Penambahan Truk Pada Distributor Semen Dengan Metode AHP dan TOPSIS - Rahmi Yuniarti; Wifqy Azlia; Umroh Fitriana (Jurnal Ilmiah Teknik Industri, 2018)
The cement distributor has a cement warehouse in Pasuruan. Cement warehouse always ready to be shipped to a regular customer. Current demand from customers remains unfulfilled because the number of corporate modes of transportation is not proportional to the number of cement demand. Thus, the company plans to add the truck with two alternatives of buying new trucks or renting Hino Ranger FG 235 JJ. To determine the best alternative, an assessment of the criteria for the addition of trucks is required. In this study AHP is used to determine the level of importance among the criteria, assess the criteria of discounts, shipping security, corporate attributes listed in vehicles, cost, age, administration, maintenance, risk of damage, availability. The result of the criteria weighting is used as the input for the selection of the best alternative in the TOPSIS method. The results obtained from the calculation of TOPSIS for alternative purchase of a new truck and renting that have value of 0.599 and 0.401.